Verso l’integrazione dei dati dei Beni Culturali: la piattaforma SACHER La valorizzazione dei Beni Culturali attraverso il cloud computing - Bertacchi, Silvia; Dall'Osso, Giorgio; Montanari, Rebecca; Torello, Marco (Archeomatica, 2018)
Digital innovation has simplified the management of the conservation-restoration of Cultural Heritage. However, it is still lacking an advanced ICT platform that can support the entire Cultural Heritage data life-cycle management and that can take into account the restoration and safeguarding works necessary to ensure also engagement and participation of both specialised experts and citizens/ tourists. SACHER project aims to fill up this gap with an innovative ICT platform based on a fully open source distributed and cloud computing infrastructure that provided web oriented and user friendly services for cultural data visualisation, searching and retrieval and that integrates existing dataset, facilitating storage and use of data relating to Cultural Heritage for both specialized and common users.